AVAILABILITY OF LABORATORY SUPPORTING STAFF AND ITS EFFECT ON THE CONDUCT OF BIOLOGY PRACTICAL LESSON AMONG PUBLIC SECONDARY SCHOOLS IN SOKOTO STATE, NIGERIA - Bello, Shamsudeen (Sokoto Educational Review, 2015)
The study has investigated availability of laboratory supporting staff and its effect on the conduct of biology practical lesson among public secondary schools in Sokoto State, Nigeria. The study answered two research questions and one hypothesis. The population of the study comprised 32 senior secondary schools in Sokoto metropolis with 93 biology teachers. Fifteen (15) public secondary schools were randomly selected with 30 biology teachers as sampled teachers, including heads of biology departments. The study used an instrument titled Biology Laboratory Practical Work Questionnaire (BLPWQ) with reliability coefficient of 0.82. Data obtained from the field were analyzed using simple descriptive statistics and chi-square. The findings revealed that public schools in Sokoto metropolis have no sufficient laboratory supporting staff. The schools also conduct little practical lessons. Similarly, there was significant relationship between laboratory supporting staff availability and frequency of conduct of biology practical lessons. It’s recommended that, the government should provide adequate and qualified laboratory supporting staff (laboratory assistant, technician/attendant) to the secondary schools in the state.